ANALISIS PERAN AKTOR DALAM KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR JALAN TAX ON LOCATION (TOL) GILIMANUK-MENGWI - Suprianta, I Made Agus; Apriani, Kadek Dwita; Noak, Piers Andreas (Jurnal Nawala Politika, 2022)
This study examines the Role of Actors in the Tax Road Infrastructure Development Policy for the Gilimanuk-Mengwi location in Yeh Cangi Selatan subak. In this regard, the author conducted research related to how the policies and methods used by the actors in supporting the established policies, especially in this development policy, there were private parties participating in its implementation. The results explain how the three parties, namely the community, government, and the private sector, are involved in the policy process. The design theory is how the approach before policy in policy theory, namely synamic framing is carried out by an approach by the development initiator to the subak community, the next step is to design dynamically at this stage there is a clash of information after the approach by the development initiator which is carried out through mass information media socialization, with dynamic translation at this stage. The second theory seeks rent through existing cultural values so that development must be in accordance with the culture of the Balinese people.